Bridging the Gap Between Practice and Concept: A School-Based Community Empowerment Model for Integrating Circular Economy into Education Management in Indonesia - Ali Hasan; Nur Salim; Trya Rafa' Nazahah (UIN Siber Syekh Nurjati Cirebon, 2026)
Waste generation has emerged as one of the most urgent global crises, with over 2.2 billion tons produced annually worldwide and projections reaching 3.4 billion tons by 2050. Indonesia alone contributes more than 68 million tons each year, yet only a fraction is properly managed. Shockingly, despite growing initiatives in schools, such as eco-programs and recycling competitions, conceptual awareness of circular economy principles remains fragmented. This paradox—high levels of participation in practical waste management alongside limited systemic understanding—reveals a critical gap in sustainability education. Theoretically, this study positions itself within the global debate on circular economy transitions, while policy-wise it responds to the absence of integration between circular economy principles and education management in Indonesia. The research aims to develop a novel model that embeds circular economy practices into school management systems through community empowerment. Using a qualitative multiple case study approach, data were collected from State Senior High School 1 Indramayu and State Vocational School 1 Majalengka through surveys, interviews, observations, and document analysis, involving teachers, students, and parents as core actors. Findings indicate that while both schools demonstrate strong practices in waste segregation, recycling, and eco-entrepreneurship, systemic barriers—structural, managerial, and cultural—impede full integration into curriculum and policy. A key contribution is the formulation of a participatory model through the School Environmental Management Unit (UPLS), which extends circular practices beyond the school to households, increasing waste recovery by 42%. The study recommends future research on broader school types and long-term policy adoption, emphasizing collaborative, cross-sectoral governance as essential for embedding circular economy education. Keywords: Circular Economy, Education Management, School Community Empowerment, Waste Management, Sustainable Education